2008
DOI: 10.1002/elps.200700947
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanotube disposable detectors in microchip capillary electrophoresis for water‐soluble vitamin determination: Analytical possibilities in pharmaceutical quality control

Abstract: In this work, the synergy of one mature example from "lab-on-chip" domain, such as CE microchips with emerging miniaturized carbon nanotube detectors in analytical science, is presented. Two different carbon electrodes (glassy carbon electrode (GCE) 3 mm diameter, and screen-printed electrode (SPE) 0.3 mm x 2.5 mm) were modified with multiwalled carbon nanotubes (MWCNTs) and their electrochemical behavior was evaluated as detectors in CE microchip using water-soluble vitamins (pyridoxine, ascorbic acid, and fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 30 publications
0
58
0
Order By: Relevance
“…[10] Escarpa et al have proposed microchip electrophoresis coupled with electrochemical detection for the separation and quantification of water-soluble vitamin. [13] To date, microchip electrophoresis for the real food sample analysis is still in its infancy, and usually involves the utilization of high voltage for the separation of samples. [14] Another option for working under complex sample matrices is to develop enzymebased methods to selectively sense AA.…”
Section: Introductionmentioning
confidence: 99%
“…[10] Escarpa et al have proposed microchip electrophoresis coupled with electrochemical detection for the separation and quantification of water-soluble vitamin. [13] To date, microchip electrophoresis for the real food sample analysis is still in its infancy, and usually involves the utilization of high voltage for the separation of samples. [14] Another option for working under complex sample matrices is to develop enzymebased methods to selectively sense AA.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Crevillén et al describe a small increase of S/N for ascorbic acid using carbon screen-printed electrode modified with multiwalled carbon nanotube (MWCNT), but this parameter was duplicated for folic acid [39]. Moreover, in another work, a noticeable improvement of S/N (420%) was reported for some polyphenols even in the analysis of real samples using the same electrode [16].…”
Section: Fundamentalsmentioning
confidence: 99%
“…The underlying bulk electrode is modified with CNT film, usually by the deposition of a suspension of CNTs in solvent (e.g. DMF or aqueous solution of a polymer) and allowing the solvent to evaporate [16,34,35,39,[43][44][45][46][47]. The CNTs consequently create a random CNT films on the surface of the electrodes.…”
Section: Carbon Nanotube-film Electrodesmentioning
confidence: 99%
See 1 more Smart Citation
“…With the appearance of carbon nanotubes (CNTs), recent electrochemical studies have revealed that CNTs can facilitate the oxidation of AA at a low potential, and demonstrated possible application of CNTs for selective determination of AA [13]. Crevillén et al developed carbon nanotube-modofied disposable detectors in microchip capillary electrophoresis for AA determination in pharmaceutical quality control [14]. However, Most of the above mentioned mehods showed a certain degree of complexity in the phase of electrode modification.…”
Section: Introductionmentioning
confidence: 99%